2016
DOI: 10.5897/err2015.2610
|View full text |Cite
|
Sign up to set email alerts
|

Observation of multimedia-assisted instruction in the listening skills of students with mild mental deficiency

Abstract: This study was carried out with 2 students with mild mental deficiency, one in 5 th grade and the other in 6 th grade of Turgut Özal Secondary School in Bulanık County of Muş Province. It was done during the spring semester of the 2014-2015 school year in order to observe the effect of multimedia-assisted instruction on listening skills of mainstreamed students with mild mental deficiency. The courses were taught in the information and communication technologies classroom outside the course hours with permissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Learning using the Brain-Based Learning model assisted with Animation can arouse students' enthusiasm for participating in learning and increase student activity in the learning process. In line with this Erhan (2016) revealed that the animation watched by students made them enjoy the lesson and became active participants in the listening process.…”
Section: Resultssupporting
confidence: 59%
“…Learning using the Brain-Based Learning model assisted with Animation can arouse students' enthusiasm for participating in learning and increase student activity in the learning process. In line with this Erhan (2016) revealed that the animation watched by students made them enjoy the lesson and became active participants in the listening process.…”
Section: Resultssupporting
confidence: 59%
“…Surajudeen et al (2023), in contrast to his study, which showed that SEN students were ready to use assistive technology and had high self-efficacy, the present study revealed that teachers needed support for the effective use of technology in educational settings. Moreover, it is stated in the literature that teachers use technology in inclusive classrooms and that integrating technology into lessons makes lessons more enjoyable and results in positive feedback from students and parents (Akın, 2016). Moreover, statements that visuals and technology accelerate SEN students' learning took place in some studies and it is also found that teachers use technology to plan lessons and embody the learning process for SEN students (Sökmen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%